Perilaku Konsumtif Menurut Etika Bisnis Islam - Anugrahi Putri Ziyadatin Ilmi; Silvi Indah Nurvita Sari; Hikmatus Sa'diyah; Ananta Delyana Mafikah; Rika Nur Amelia; Eny Latifah (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
In Indonesia, the increasing consumer behavior is caused by globalization and a culture of materialism, which poses significant moral and economic challenges. The purpose of this research is to explain how Islamic business ethics influence the consumer behavior of society. This study uses library research with a descriptive method. This involves literature research related to journals, books, and scientific articles. Research shows that Islamic business ethics, based on Sharia values such as justice, balance, and social responsibility, can serve as a useful foundation for transforming consumer behavior to be more rational and aligned with needs. The results show that the values of Islamic business ethics should be incorporated into economic policies, education, and business practices in Indonesia to create a more prosperous and moral society.